Men and women on air : gender stereotypes in humour sequences in a Malaysian radio phone-in programme - Yoong, Melissa (Equinox Publishing, 2017)
This paper investigates the use of humour in a Malaysian radio phone-in programme to reinforce or challenge stereotypical conceptualisations of men and women. It is argued that these acts of humour uphold gender hierarchies and inequalities in a few ways. Traditional stereotypical portrayals of women still prevail, and these characteristics are naturalised by appealing to assumed shared common sense. Although both sexes are mocked in some instances of humour, when analysing why men and women are ridiculed, it was found that the men were targeted for two conflicting reasons: for exhibiting stereotypical feminine characteristics and for attempting to produce a hegemonic masculine identity. On the other hand, women were mocked for embodying traits culturally ascribed to masculinity. It is concluded that this works to legitimate men’s social dominance over women.